Socially Responsible Leadership and Job Engagement in University Context: Mediation of Psychological Safety - Kyambade, Mahadih; Namatovu, Afulah; Mugambwa, Joshua; Namuddu, Regis; Namubiru, Bridget (SEISENSE (PRIVATE) LIMITED, 2024)
Purpose - This study looks into the connection between job engagement (JE) and socially responsible leadership (SRL) in public universities in Uganda.Methodology - The study is quantitative in nature and consisted of personnel working at Uganda's public universities supplied data. The information was gathered using a five-point Likert scale in an organized questionnaire. Expert judgment and content validity were used to assess the validity of the instrument. Warp PLS and smart PLS-SEM analysis was run on 214 legitimate responses among 250 public university staff. Findings - The findings demonstrated a positive correlation between JE and SRL. PS and SRL were found to be positively correlated. Furthermore, the results showed a positive correlation between PS and JE. Additionally, the findings demonstrated that PS acts as mediation in the relationship between SRL and JE. Originality – The study contributes to the understanding of the approaches related to improving employee job engagement in the education sector. The study adds to the body of knowledge concerning the association between job engagement and psychological safety a crucial aspect of socially responsible leadership by examining data from developing countries in addition to other countries which had previously been ignored. Practical implications - This study contributes to the corpus of research on SRL and PS, especially in the context of universities, in terms of JE. Additionally, it provides advice on how to use PS and SRL to enhance university workplace conditions such as JE. By emphasizing the crucial roles that a psychologically safe environment and leadership style that is socially responsible play in promoting positive social interactions at work, our article advances the understanding of social exchange theory.